Virtual exhibition: a non fungible token (NFT) / Perpustakaan Tengku Anis - UiTM Kelantan, Perpustakaan Tengku Anis (Perpustakaan Tengku Anis (PTA), 2022)
A non fungible token (NFT) cryptographic assets on a blockchain with unique identification codes and metadata that distinguish them from each other. NFT cannot be traded or exchanged, unique cryptographic tokens that exists on a block chain, can represent real world items, functioning in represent individuals property rights, identities and etc. "Tokenizing" these real world tangible assets makes trading, selling and buying more efficient while reduce the fraud.